Stink bug on tomatoes: Injury and its prevention investigated in last season's outbreak in Yolo and Sacramento counties - A Michelbacher; W Middlekauff; O Bacon (California Agriculture, 1952)
Several tomato fields in California showed severe stink bug damage this past season.